Prenatal detection and molecular cytogenetic characterization of 19q13.42 microduplication: three reported cases and literature review - Zhang, Xinyue (Mol Cytogenet, 2021)
BACKGROUND: Trisomy 19q is a recognizable syndrome and associated with a wide spectrum of clinical phenotypes in clinic. The purpose of this study was to explore the prenatal phenotypes of 19q13.42 duplication, which was rarely reported in clinic. CASE PRESENTATION: Three pregnant women presenting diverse indications for prenatal diagnosis accepted amniocentesis: increased nuchal translucency and fetal pyelic separation (case 2) and high risk of maternal serum screening for Down syndrome (case 1 and case 3). Case 1 and case 2 shared similar duplicated locus in the region of 19q13.42, encompassing part NLRP12 gene. The latter inherited the chromosomal duplication from the mother with normal phenotypes. Case 3 carried a 1.445 Mb duplication in the 19q13.42q13.43 region. It was proposed that evolutionary duplication of NLRP12 gene could have a causative role in autoinflammatory diseases development. The genotype–phenotype correlation depends mainly on the duplicated size and functional genes involved, which is still yet to be determined. All pregnant women chose to continue the pregnancy and delivered healthy children with no apparent abnormalities. CONCLUSIONS: The 19q13.42 microduplications in our study were the smallest fragments compared to previous literature. Our findings enriched the prenatal phenotypes for this chromosomal microscopic imbalance. It was proposed that long term follow up analysis should be guaranteed till adulthood to determine whether there will be other emerging clinical symptoms and developmental-behavioral disorders for such carriers.